Eksplorasi Pengalaman Perawat Memberikan Posisi Duduk dalam Pelukan Orang Tua Selama Insersi Intravena: Studi Kualitatif - Ni Made Sri Rahyanti (JURNAL KEPERAWATAN RAFLESIA, 2022)
Intravenous insertion with parental holding and upright position reduces pain and anxiety in young children. This position has not been routinely applied by nurses, even though several nurses have been introduced and carried out this position. The aim of this study was to explore nurses experience gave “parental holding and upright position” during insertion intravenous procedure. This study used phenomenology qualitative study. The number of samples in this study were 10 nurses with inclusion criteria is nurse who had given parental holding and upright position while intravenous insertion. Exclusion criteria is nurse who was not present at the interview due to illness. Data collected through in-depth interviews. Based on the interview, it was found theme “intravenous insertion procces is more enjoyable”. Nurses found it easier to work because children are comfortably restrained by their parents, and children are more comfortable when their parents hug them. This position provides a positive thing for both nurses and children. The parental holding and upright position can be used as a routine position by nurses when carrying out intravenous insertion procedures because through this position the nurse and young children become more comfortable during the procedure.